2012
DOI: 10.1186/1471-2407-12-359
|View full text |Cite
|
Sign up to set email alerts
|

Protein markers of cancer-associated fibroblasts and tumor-initiating cells reveal subpopulations in freshly isolated ovarian cancer ascites

Abstract: BackgroundIn ovarian cancer, massive intraperitoneal dissemination is due to exfoliated tumor cells in ascites. Tumor-initiating cells (TICs or cancer stem cells) and cells showing epithelial-mesenchymal-transition (EMT) are particularly implicated. Spontaneous spherical cell aggregates are sometimes observed, but although similar to those formed by TICs in vitro, their significance is unclear.MethodsCells freshly isolated from malignant ascites were separated into sphere samples (S-type samples, n=9) and mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 50 publications
2
50
2
2
Order By: Relevance
“…However, co-culture of the ovarian cancer cells with MSC was associated with EpCAM mRNA and protein induction, which suggested certain differentiation processes by adding epithelial celllike properties to the MSC. Such heterogenic functionality was also discussed in vivo with EpCAM-positive subsets of tumor-initiating cells (cancer stem cells) in patient ovarian cancer ascites also carrying markers of cancer-associated fibroblasts [44]. Other in vivo studies demonstrated crosstalk of MSC with tumor cells and promotion of tumor growth in patients with head and neck cancer, whereby MSC isolated from these patient tumors constitutively produced high levels of IL-6, IL-8, and stromal cell-derived factor (SDF)-1a [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, co-culture of the ovarian cancer cells with MSC was associated with EpCAM mRNA and protein induction, which suggested certain differentiation processes by adding epithelial celllike properties to the MSC. Such heterogenic functionality was also discussed in vivo with EpCAM-positive subsets of tumor-initiating cells (cancer stem cells) in patient ovarian cancer ascites also carrying markers of cancer-associated fibroblasts [44]. Other in vivo studies demonstrated crosstalk of MSC with tumor cells and promotion of tumor growth in patients with head and neck cancer, whereby MSC isolated from these patient tumors constitutively produced high levels of IL-6, IL-8, and stromal cell-derived factor (SDF)-1a [45].…”
Section: Discussionmentioning
confidence: 99%
“…They are also morphologically identified as spindleshaped cells scattered in the tumor stroma [28]. Although a series of molecular markers have been identified, none are unique to CAFs [29]. However, increasing evidence has revealed the association between mCAFs and poorer survival in breast cancer patients or an aggressive tumor phenotype (Table 1).…”
Section: Cafs In Breast Cancer Progressionmentioning
confidence: 99%
“…Numerous studies have found that cancer-associated fibroblasts (CAFs) play an important role in a wide variety of tumors, such as breast, prostate, esophageal, pancreatic and lung cancer by promoting the initiation, proliferation, invasion and metastasis of cancer cells; however, the underlying mechanisms are not yet fully understood (6)(7)(8)(9). In our previous studies, we found that the abundance of CAFs in ovarian cancer is associated with the advanced stage of the tumor, lymph node metastasis and omental metastasis.…”
Section: Introductionmentioning
confidence: 99%